دور الدولة وآلياته في اقتصاد السوق الاجتماعي في سورية دراسة مقارنة مع بعض التجارب العالمية - قنوع نزار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إذا كان لدور الدولة في الحياة الاقتصادية عموماً ما يبرره، فإن هذا الدور يصبح أكثر ضرورة ووجاهة في إطار ما يسمى اقتصاد السوق الاجتماعي، وذلك لأسباب كثيرة لعل أهمها أن الدولة بما لديها من سلطات أكثر قدرة على لعب دور المخطط والمنظم والمراقب في إطار هذا السوق. وفي هذه الدراسة سنقوم بمناقشة وتحليل هذا الدور، وكذلك جوهر وفلسفة اقتصاد السوق الاجتماعي، وخصوصية الاقتصاد السوري ومعالم مشكلته الاقتصادية. ثم نسلط الضوء على مسألة الإصلاح الاقتصادي وتصوراته، يلي ذلك استعراض لبعض التجارب العالمية في هذا المجال وإمكانية الاستفادة منها في الواقع السوري، لنخلص في النهاية إلى وضع الاستنتاجات والتوصيات التي يمكن أن تسهم في حل إشكاليات هذا الموضوع. If the state’s role in economic life in general is justified, this role becomes more necessary and relevant in the context of the so-called social market economy. This is for many reasons, perhaps the most important one is that the state, including its authority, has more ability to play the role of planning, organizing and observing in the context of this market. In this study, we will discuss and analyze this role, as well as the essence and philosophy of the social market economy, and the specificity of the Syrian economy and economic parameters of this problem. Then we highlight the issue of economic reform and perceptions, followed by review of some international experience in this area and benefiting it in Syria, and then coming to an end to develop conclusions and recommendations that could contribute to resolving this problematic issue.